Human-computer etiquette : cultural expectations and the design implications they place on computers and technology - Hayes, Caroline; Miller, Christopher Allan (Supply chain integration series., 2011)
Written by experts from various fields, this edited collection explores a wide range of issues pertaining to how computers evoke human social expectations. The book illustrates how socially acceptable conventions can strongly impact the effectiveness of human-computer interactions and how to consider such norms in the design of human-computer interfaces. Providing a complete introduction to the design of social responses to computers, the text emphasizes the value of social norms in the development of usable and enjoyable technology. It also describes the role of socially correct behavior in technology adoption and how to design human-computer interfaces for a competitive global market.